(untitled) (INNOVATIVE ECONOMY, 2020)
Bakun Yu.O. MANAGEMENT AND ADVISORY MECHANISMS FOR CLIMATE CHANGE LEVELLING Purpose. The aim of the article is the comparison of management and advisory mechanisms for climate change leveling and determination the most significant groups on this basis. Methodology of research. The methodological basis of research consists of methods of comparison and generalization. The comparison of separate management and advisory mechanisms for climate change leveling was fulfilled using the comparison method. Five most significant groups of mechanisms for climate change leveling have been determined on the base of generalization method. Findings. The necessity of deepening participation at different management levels in Ukraine in solving the global warming problem is substantiated on the basis of actualization of management and advisory mechanisms for climate change leveling. It will contribute both solving the problem itself and increasing the international authority of the state. The advisability of realization of measures for climate change leveling is confirmed at the different levels: at governance levels (state, regional, sectoral, enterprise) and by leveling directions (population and business entities). The international management and advisory mechanisms for climate change leveling with identification of five characteristic groups has been generalized. The importance of solving the problem at the different management levels with use of advisory services is proved. It will permit more efficient implementation of advisory mechanisms and reach a wider coverage of solving of the tasks of climate change leveling. Originality. The international management and advisory mechanisms for climate change leveling has been generalized with identification of five characteristic groups: organizational (international organizations), regulatory and legal (conventions, resolutions, declarations), coordinating (conferences, meetings), financial and business (emission limits, environmental taxes), programs and models (models, scenarios, programs, strategies). This, unlike the existing one, gives an opportunity of its differential use in the process of preparing more substantiated management solution of the indicated problem. Practical value. The results of the research can be used in the process of preparing of strategic and program documents of an environmental nature. The effect of its implementation can be estimated by indicators of environmental improvement, in particular by indicators of reducing greenhouse gas emissions, etc. Key words: climate change, climate change leveling, management mechanisms, advisory mechanisms, groups of mechanisms for climate change leveling, agricultural advisory services.